What More to do to Make Online Teaching an Attractive and Effective Tool for Medical Students? An Experience from a Rural Tertiary Care Institute in Haryana State, India - Verma, Ramesh Kumar; Verma, Vijay Kumar (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: Though online teaching-learning methodology is not a new way of transferring knowledge and skill, however pandemic of COVID-19 has made it more relevant to all fields. Medical education is majorly dependent on patients and related resources. However, the current pandemic has pushed the medical fraternity to use online methods. Understanding the perception of end-users (medical students) may help get the best out of this methodology. Hence, we planned this study to know medical students' perception of the online teaching-learning methodology. Methods: The present cross-sectional study was executed among the undergraduate medical students, from the first year to final year, of Bhagat Phool Singh, Government Medical College for Women, Khanpur Kalan, Sonepat of Haryana state, India. The data were collected through a semi-structured questionnaire sent to all students as a link to Google form. The study sample was selected through stratified random sampling. We assumed every batch of students as a stratum and randomly selected 25 students from each batch; hence, data analysis from 100 students was conducted. Results: Most participants found the online teaching-learning methodology comfortable, time and money-saving. However, almost all of them refuted online methods for clinical or bedside teaching. Family distractions, internet connectivity, physical discomfort, isolated feeling, and poor interaction among peers were reported as barriers to online methods. Conclusions:Selective use of online teaching-learning methodology with inbuilt peer interaction has enormous potential in medical education.